Критерії оцінки ефективності інвестиційно-організаційного забезпечення розвитку підприємств машинобудівного комплексу - Тонкіх, Е. І. (НТУ "ХПІ", 2014)
Визначено значення та вплив інвестиційно-організаційного забезпечення на ефективність роботи машинобудівних підприємств. Визначені принципи та критерії оцінки ефективності інвестиційно-організаційного забезпечення розвитку підприємств машинобудівного комплексу з метою активізації інвестиційної діяльності. Доведено, що створення сприятливого інвестиційного середовища та посилення механізму мотивації довгострокового вкладення коштів пов'язане з використанням як ринкових заходів, так і заходів щодо централізованого державного регулювання інвестиційної діяльності.

The values and the impact of investment and organizational support of the efficiency of the machine-building enterprises. Defines the principles and criteria for evaluating the effectiveness of investment and organizational support of the development of machine-building enterprises to enhance investment activities. It was revealed that the main purpose of investment and organizational security is a certain direction, methods, means and forms of investment in order to improve efficiency and increase the profits of enterprises. To be effective investment machine-building enterprises is an important consideration and use of methodological principles for investment activity of enterprises. It is proved that the creation of a favorable investment environment and strengthen the motivation mechanism of long-term investments due to the use of market-based measures as well as measures for the centralized state regulation of investment activity.
Criteria for evaluating the effectiveness of investment and organizational support of the development of machine-building enterprises
Keywords: машинобудівні підприємства; машинобудівний комплекс; інвестиційно-організаційне забезпечення; інвестиційне середовище; investment and organizational support; machine-building complex